Epitaxy and characterization of AlGaInP-based LEDs on Si substrates for visible-spectrum light emission - Wang, Cong (2017)
This research work is aimed to epitaxially integrate (Al)GaInP compounds on silicon (Si) platform for visible-light (red, yellow, and green) LEDs. The integrated LED on Si not only reduces fabrication cost, but also enables many novel applications, such as a CMOS-driving LED system. However, several research gaps exist in the integration processes, in terms of epitaxy quality, green-light LED efficiency, and LED performance on Si. This research work was mainly focused on the following topics to address the these research gaps: (1) epitaxy of high-quality III-V compounds on Si by employing graded buffers and optimising growth conditions, (2) development of band engineering techniques to enhance the luminescence efficiency of indirect band GaInP alloys for green light emission, and (3) fabrication and characterisation of multi-colour LED on Si. This work will represent promising pathways towards the epitaxial integration of III-V photonics on Si platform.